Revisiting Tax Avoidance in Global Islamic Commercial Banks: The Critical Role of Profitability, Capital Structure, and Firm Size within a Sharia-Based Governance Framework - Hadi Purnomo; Nicko Albart; Kurniati Karim; Listiana Sri Mulatsih; Alfiana (IQTISHODUNA: Jurnal Ekonomi Islam, 2025)
Tax avoidance remains a persistent concern in the global banking industry, including Islamic commercial banks, where financial decision-making is expected to align with Shariah-based governance principles. This study revisits the determinants of tax avoidance in Islamic commercial banks by critically examining the roles of profitability, capital structure, and firm size within a Shariah-compliant institutional context. Employing a quantitative research design, this study analyzes panel data from nine Islamic commercial banks that consistently published quarterly financial reports from 2018 to 2022. The empirical analysis is conducted using panel regression techniques in EViews 10, supported by classical assumption tests, model feasibility tests, and coefficient-of-determination analysis. The findings reveal that profitability and capital structure significantly Influence tax avoidance behavior in Islamic commercial banks, while firm size does not exhibit a statistically significant effect. These results suggest that internal financial performance and leverage decisions play a more decisive role than organizational scale in shaping tax-related behavior, even within Shariah-oriented institutions. The novelty of this study lies in its integration of conventional financial determinants with a Shariah-based governance perspective, offering critical insights into how Islamic banks navigate the tension between profit optimization and ethical tax compliance. The findings contribute to the global Islamic economics literature by providing policy-relevant implications for strengthening governance mechanisms and enhancing fiscal responsibility in Islamic financial institutions.